Cloning and developmental expression analysis of ltd-1, the Caenorhabditis elegans homologue of the mouse kyphoscoliosis (ky) gene. - Vargas, J; Culetto, E; Ponting, C; Miguel-Aliaga, I; Davies, K; Sattelle, D (2002)
We have characterized the developmental expression pattern of the Caenorhabditis elegans homologue of the mouse ky gene. The Ky protein has a putative key function in muscle development and has homologues in invertebrates, fungi and a cyanobacterium. The C. elegans Ky homologue gene has been named ltd-1 for LIM and transglutaminase domains gene. The LTD-1::GFP construct is expressed in developing hypodermal cells from the twofold stage embryo through adulthood. These data define the ltd-1 gene as a novel marker for C. elegans epithelial cell development.